FRI0406 Small LDL-P Increases with Increased Disease Activity in SLE. (9th June 2015) - Durcan, L.J.; Winegar, D.; Connelly, M.A.; Otvos, J.; Magder, L.; Petri, M.
Abstract : Background: Systemic lupus erythematosus (SLE) associates with accelerated atherosclerotic cardiovascular (CV) disease which is not fully explained by traditional CV risk factors. Disease activity, prednisone treatment and immunologic abnormalities are also thought to contribute. Dyslipidemia is common in SLE patients, who have mild elevations in triglycerides (TG) and sometimes low HDL cholesterol levels. Recent evidence suggests that low density lipoprotein particle number (LDL-P) is a better marker of cardiovascular risk than LDL cholesterol levels. Lipoprotein subclass analyses have shown that SLE patients have larger VLDL particles and lower levels of large HDL particles compared to control subjects, but little is known about how these markers change with disease activity. Objectives: We evaluated SLE patients during high disease activity and compared this to no or low disease activity to determine how lipoproteins change with active SLE. Methods: Patients were identified as part of a prospective lupus cohort. At each visit, plasma samples were collected. Global disease activity was measured using the SLEDAI. Patients were included who had at least one visit with SLEDAI of 4+ (high disease activity) and one visit with SLEDAI≤3 (low disease activity). Plasma was analyzed for lipoprotein particle concentrations using nuclear magnetic resonance spectroscopy (NMR). The NMR spectrum also contains a signal termed GlycA derived from the carbohydrate chains of circulating acute phase glycoproteins that is a marker of systemic inflammation. Lipoprotein particle and GlycA levels were compared between high activity and no or low disease activity visits using t-tests. Results: 33 patients met inclusion criteria (97% female, age range 19-76, 48% Caucasian and 48% African American). The mean number of visits per person with high Vs. low disease activity were 2.1 and 2.4 respectively. The total LDL particle number (LDL-P) and small LDL-P levels were higher with disease activity as was VLDL size (Table 1 ). Although GlycA levels were unchanged with active disease, they were higher than those described for healthy populations. Conclusions: Although the lipoprotein profiles of SLE patients have been previously described, alterations in these profiles with disease activity have not been investigated. Here we demonstrate, for the first time in adult SLE, adverse changes in one novel lipid parameter (small LDL-P) with disease activity. Thus, we can now demonstrate one potential mechanism by which SLE disease activity influences atherosclerosis. Disclosure of Interest: None declared